Clinical and histopathological study of lepra reactions from a tertiary care center in South India - Prasannan, Remya; George, Mamatha; M. P., Binitha; T., Lekha (International Journal of Research in Dermatology, 2017)
Background: Clinical features and histopathology of leprosy and type 1 and type 2 reactions do not always match, though they are generally accepted as important for arriving at a diagnosis. We studied the varied clinical presentations and the correlation with histology in patients presenting with leprosy and type 1 and type 2 reactions. Methods: All patients with clinical features of leprosy and those with features of type 1 and type 2 lepra reactions attending the department of Dermatology from August 2008 to August 2009 were included. Detailed history, clinical examination and skin biopsy findings were noted and correlated using descriptive statistics. Results: Of the 138 patients included in the study, 24 cases of reactions were detected. Eighteen had type 1 (75%) and six had type 2 (25%) reaction. Correlation showed that dermal edema on histology was helpful in diagnosis of lepra reactions while neutrophilic infiltration favoured the diagnosis of type 2 reactions. Conclusions: Histopathological features are helpful in the diagnosis of lepra reactions, however in cases of doubt, the diagnosis should be made on clinical grounds.